Social work with drug, alcohol and substance misusers - Goodman, Anthony (Anthony Harvey) (Transforming social work practice, 2013)
It has long been recognised that clients with addiction problems need a skilled and thoughtful response when they come into contact with social services. This new edition will help students to cultivate these skills with sections on anti-oppressive practice and a focus on service user empowerment. Case studies and reflective exercise will focus the student on this holistic approach while underpinning key learning objectives. With a new focus on social work practice with alcohol misusers, this third edition provides a firm foundation for the skills required when working with people with drug and substance addictions.